Higher Education Strategic Partnership Management Model for the Independent Campus Internship - Aziz, Suudin; Sahri, Sahri; bin Mohd Saufi, Mohd Shahid Azim (JURNAL AL-TANZIM, 2025)
This study aims to analyse the ideal strategic partnership model for implementing the Independent Learning Campus Internship (MBKM) program in higher education. Systematic and sustainable partnership management is crucial for optimally supporting the implementation of the MBKM program. The research approach employed was a descriptive qualitative one, utilising data collection techniques that included in-depth interviews, observation, and documentation studies. The results indicate that despite the existence of a basic MBKM implementation structure, challenges such as limited documentation, suboptimal training, and weak evaluation of collaboration remain significant obstacles. This study led to the development of a strategic partnership model comprising four main pillars: collaborative planning, institutional organisation, internship program implementation, and evaluation and sustainability of the collaboration. Two key components strengthen this model: enhancing the digitalisation system and fostering an ethical and inclusive partnership culture. The implementation of this model is expected to improve the effectiveness of collaboration, strengthen student competencies, and enhance the institution's reputation through sustainable and career-relevant partnerships.